Effect of intra-session exercise sequence on the load-velocity relationship variables after a concurrent sprint interval and resistance training program - Pérez-Castilla, A.; García-Pinillos, F.; Ramirez-Campillo, R.; Ruiz-Alias, S. A. (International Journal of Sports Science & Coaching, 2023)
This study aimed to examine the effects of altering the intra-session exercise sequence of a concurrent training program on the load-velocity relationship variables obtained from different compound exercises. Physically active subjects (n = 24, age = ~21 years) were assigned to one group that performed sprint interval training (sprints: 4-6; intensity: all-out; duration: 30 s; rest: 4 min) followed by resistance training (exercises: back squat and bench press; sets per exercise: 4-6; load: 60-80% of the one-repetition maximum; repetition in reserve: 6-1; rest: 2 min) (SIT + RT) or another group that performed the opposite sequence (RT + SIT). Exercises modes were separated by 10 min. Both groups trained three times per week over an eight-week period. The individualized load-velocity relationships were assessed before and after training through an incremental loading test during the back squat and bench press exercises and three variables were subsequently calculated: load-axis intercept (L0), velocity-axis intercept (v0), and area under the line (Aline = L0·v0/2). Regardless of exercise sequence, both groups increased L0 (ES range = 0.78-0.91) and Aline (ES range = 0.50-0.55) but decreased v0 (ES range = -0.36 to -0.46) during the back squat exercise, while all load-velocity relationship variables were increased (ES range = 0.04-2.20) during the bench press exercise. The SIT + RT group showed a moderately greater bench press v0 increase compared to the RT + SIT group (ES = -1.07). These results indicate that both intra-session exercise sequences can induce comparable improvements in the load-velocity relationship variables after an eight-week concurrent training program.